Association between depressive symptoms and parental stress among mothers and fathers in early parenthood: A Swedish cohort study. (2nd January 2016) - Kerstis, Birgitta; Nohlert, Eva; Öhrvik, John; Widarsson, Margareta
Abstract: Aim To determine whether there is an association between depressive symptoms and parental stress among mothers and fathers during early parenthood in Sweden. Methods In this study, 401 mothers and 396 fathers (393 couples) were included; the Edinburgh Postnatal Depression Scale and the Sense of Coherence Scale were measured 3 months after childbirth, and the Swedish Parenthood Stress Questionnaire and the Sense of Coherence Scale after 18 months. Complete data for multivariable analysis were available for 264 mothers and 252 fathers. Results The mothers estimated greater total depressive symptoms and parental stress than the fathers did. Both the mothers and the fathers had the greatest level of stress in the sub-area 'Role restriction'. The mothers had the lowest level of stress in the sub-area 'Social isolation' and the fathers in the sub-area 'Incompetence'. The mothers perceived greater levels of stress than the fathers did in all sub-areas except for 'Social isolation', where the fathers perceived higher stress. There was an association between the parents' depressive symptoms and parental stress. The parents' own depressive symptoms at 3 months and sense of coherence and the partners' parental stress at 18 months were positively associated with the parental stress at 18 months in univariable and multivariable analyses. Conclusions Understanding the relationship between depressive symptoms and parental stress is important for health professionals so they can offer parents adequate support in early parenthood to optimize the conditions for raising a child. This knowledge should also be communicated to the parents.